(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Riddles reflecting cosmogonic and meteorological motifs are considered in the article, examples of meteoronyms used to describe natural phenomena in riddles are given, mythological view of the people in cosmogonic riddles is reflected.